STUDI KELAYAKAN INVESTASI PADA PROYEK PENINGKATAN STRUKTUR JALAN MALINAU – LONG ALANGO - Habir Habir (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
Before investors invest their capital, an investment feasibility analysis must be carried out for what research is carried out, namely to find out the capital that must be invested at this time in the hope of getting greater profits in the future. The NPV (Net Present Value) and IRR (Internal Rate of Return) methods are methods that are often used by investors to analyze the feasibility of an investment. The formulation of the problem in this paper is How much NPV (Net Present Value) and IRR (Internal Rate of Return) on the value of the project for the Improvement of the Malinau - Long Alango Road Structure of the East Kalimantan Provincial Public Works Department in the three years of 2012? How much NPV (Net Present Value) and IRR (Internal Rate of Return) if the project investment costs are obtained from bank loans?Based on the results of the analysis and discussion that if using NPV own capital is Rp. 873,203,421, 89 and IRR, which is 10.867%> 10%. While the capital using a loan from the NPV Bank was Rp. - 743,345,869, 83 <0, and IRR obtained by 9.25% <10%. means the investment appraisal of the project for the Improvement of the Malinau-Long Alango Road Structure for the Public Works Department of the East Kalimantan Province in the three regions of 2012 is feasible to do if it uses its own capital, and vice versa if all capital obtained from loans from banks is not feasible and must be reconsidered.